Different Drugs for the Treatment of Painful Diabetic Peripheral Neuropathy: A Meta-Analysis - Jingxuan, Lian; Litian, Ma; Jianfang, Fu (Frontiers in Neurology, 2021)
To systematically evaluate the effects of different drugs for the treatment of painful diabetic peripheral neuropathy. Methods: All literature from PubMed, Embase and Cochrane Central Register of Controlled Trials published over the past 12 years (from January 1, 2008 to June 1, 2020) was searched, and two reviewers independently assessed study eligibility, continuous data extraction, independent assessment of bias risk, and graded strength of evidence. The pain score was used as the main result, and 30% and 50% pain reduction and adverse events were used as secondary results. Results: A total of 37 studies were included. Pregabalin, duloxetine, tapentadol, lacosamide, mirogabalin and capsaicin were all more effective than placebo in alleviating the pain associated with diabetic peripheral neuropathy, while ABT-894 and gabapentin showed no significant effect. In addition, the efficacy of buprenorphine, tanezumab, fulranumab and others could not be concluded due to insufficient studies. Conclusion: Pregabalin and duloxetine showed good therapeutic effects on painful DPN, but adverse events were also significant. The analgesic effects of ABT-894 and gabapentin need to be further studied with longer and larger RCTs. As an opioid drug, tapentadol has a good analgesic effect, but due to its addiction, it needs to be very cautious in clinical use. Although lacosamide, mirogabalin and capsaicin are more effective than placebo, the therapeutic effect is weaker than pregabalin. For the results of our meta-analysis, long-term studies are still needed to verify their efficacy and safety in the future.